Impact of an Educational Film on Parental Knowledge of Children with Cerebral Palsy - Shilpa Khanna Arora; Anju Aggarwal; Hema Mittal (Hindawi Limited, 2014)
Parents of children with cerebral palsy (CP) must have knowledge about the disease and its management to improve the outcome. This uncontrolled interventional trial was carried out to evaluate the parental knowledge of CP and assess the impact of an educational programme on it. Preset questionnaires were filled before and 1 week after a single session educational programme using an educational film. Out of a total of 53 subjects, majority (75.5%) were from lower socioeconomic status. Initially, none knew the correct name of child's illness; afterwards 45.3% could name it. When compared to previous status, there occurred significant improvement in the knowledge of parents after viewing the film with regard to knowing the cause of CP, knowing that motor involvement was predominant in CP, knowledge regarding curability of the disease, and knowledge about special schooling (P<0.05). Change in knowledge was not related to socioeconomic or educational status (P>0.05). Majority (94.3%) found the film useful and 96.2% learned how they could help in the management of their children. Parental knowledge of CP is inadequate which can be improved by incorporating such educational programmes in special clinics to improve management.